Matrix metalloproteinase 9, superoxide dismutase and lipid peroxidation in preterm newborns with perinatal hypoxia - Yu. V. Korenovsky; S. A. Elchaninova; N. I. Fadeyeva (Бюллетень сибирской медицины, 2011)
The perinatal hypoxia (PH) in preterm newborns is associated with elevated levels of matrix metalloproteinase 9 (MMP-9), superoxide dismutase (SOD) and thiobarbituric acid reactive substances in umbilical cord blood plasma. The severity of PH Apgar scores correlated with SOD (r = –0,40; p = 0,006) and MMP-9 (r = 0,36; p = 0,023). It is assumed that the SOD increase prevents the reactive oxygen species mediated activation of MMP-9, which destroy the collagen of the basement membrane of the bloodbrain barrier.